#TITLE_ALTERNATIVE# - ANAS (NIM : 12208073), FAKHRIAL
Miocene Main Cibulakan Reservoir in X field has been identified with low resistivity problem. Low resistivity zone (Zone X-33) which is located at 3300 ft depth (MD) shows resistivity log reading ranging between 1-2 ohmm. The existence of hydrocarbon in this reservoir field has been proven by DST and several wells produced oil with low watercut. When conventional interpretation (Archie model) was conducted, thiz zone results in high water saturation (Sw) that is not considered as oil bearing zone. It is therefore important to identify low resistivity zone as early as possible in the life of a prospect. Identification of factors that cause low resistivity were investigated with some data such as RCA, SCAL, XRD, SEM, etc. One or several factors influencing low resistivity phenomena may cause problems of low resistivity. Construction of saturation model from log is performed in this study. Saturation modeling calculations include several stages, namely:environmental correction, clay volume algorithm, porosity-saturation algorithm, and validation. Environmental correction utilize Schlumberger method and clay volume established from commonly used algorithms. Porosity-saturation algorithm is an iterative scheme due to the presence of parameter Sxo as the hydrocarbon correction. Validation in this study was conducted by a different method considering data availability.